Review on DNA Modification for Drug Tartgeting Purposes - Marvelous, Solomon Godiya; Umaru, Isaac John; Umaru, Kerenhappuch Isaac (Darul Yasin Al Sys, 2024)
DNA (deoxyribonucleic acid) modification for drug targeting purposes is a rapidly advancing field that holds great promise for revolutionizing the way we approach disease treatment, offering precise and personalized approaches to tackle diseases. This seminar work provides an overview of the potential application of DNA modification for drug targeting. The seminar work begins by introducing nucleic acid and its types, structure of DNA and DNA modification, the concept of DNA modification and its significance in the context of drug targeting. It highlights the potential of DNA modification techniques, such as gene editing and epigenetic modifications. It also explores the application of DNA modification for drug targeting purposes. It discusses the use of gene editing technologies, such as CRISPR-Cas9, in correcting genetic mutations associated with inherited disorders or targeting disease-causing genes. By utilizing DNA modification techniques, drug targeting can be fine-tuned to enhance efficacy and minimize side effects. In general, this seminar report emphasizes the great potential of DNA modification for drug targeting purposes. By precisely modifying DNA, scientists can develop targeted therapies, correct genetic mutations, and optimize drug responses.